An introduction to SAGE programming : with applications to SAGE interacts for mathematics - Mezei, Razvan A., 1982- (Hoboken : Wiley, 2016)
"An Introduction to SAGE Programming: With Applications to SAGE Interacts for Numerical Methods emphasizes how to implement numerical methods using SAGE Math and SAGE Interacts and also addresses the fundamentals of computer programming, including if statements, loops, functions, and interacts"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: SageMath; Mathematics -- Data processing; Numerical analysis -- Data processing; Computer programming; MATHEMATICS -- Mathematical Analysis; Electronic books